IMPLEMENTASI PASAL 84 DAN PASAL 85 UNDANG-UNDANG NOMOR 2 TAHUN 2004 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS DI KABUPATEN SLEMAN - SAPUTRA, ADE; Haryati, Dwi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Objective of this research was to study implementation of sanction in Article 84 and Article 85 of Law number 2/2014 on amendment of law number 30/2004 on notary and effort done by notary supervisory council in following up sanction decision that is not done by notary in Sleman regency. It is juridical empirical research that based on field research data obtained from respondent and informant. The research was conducted in Sleman regency. Subject consisted of one notary doing violation and one member of Local Supervisory Council. Informant in this research is one member of Local Supervisory Council, one notary having same position as notary doing violation and one member of judge panel in Sleman district court. The research was conducted with interview and library research. Obtained data was analyzed qualitatively and presented descriptively. The result indicated that implementation of Article 84 and Article 85 Law number 2 of 2014was conducted by Local Supervisory Council based on public report or party damaged by deed made by the notary. Sanction given to notary is a punishment to notary as public officer that did not run his tasks and violation over notary violation according to rule in UUJN. Task violation of notary function causing deed he made having proving power as unofficial deed or void by law, will be punished with civil sanction before obtain decision from district court. Meanwhile mechanical violation in practicing as public officer will be punished with administrative sanction by notary supervisory council. Attempt done by notary supervisory council in following up sanction undone by notary is less affirmation of supervisory council on sanction given and less understanding of notary on notary function and prohibition as public officer.